(untitled) (African Journal of Biomedical Research, 2020)
This report investigates an outbreak of coccidiosis in a rabbitry in Ibadan, Nigeria. The rabbits were raised in a commercial breeder rabbitry with a total stock of 700 rabbits. The duration of mortality was 5 days, with an average of 140 rabbits per day giving a total of 635 (85%) mortalities. Clinical signs, necropsy findings, cytological, Histopathological and confirmatory diagnosis were reported and discussed. This case report further showed that coccidiosis in rabbitry is still a serious problem which should be monitored and controlled